2017
DOI: 10.1017/jmo.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Capacity development and Indigenous social enterprise: The case of the Rirratjingu clan in northeast Arnhem Land

Abstract: With the widespread shift from models of welfare to business-led development, capacity development offers a useful lens from which to consider the emergence of Indigenous social enterprise as a business-led development approach. We explore capacity development from the international development literature and identify capacity development principles in the context of an Indigenous social enterprise in remote northeast Arnhem Land. Here, Aboriginal Australians continue to experience poverty and marginalisation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Democratization is a term that regularly presents itself in conversations on cooperatives, yet is integral to the EMES guidelines, making it relevant across different contextual approaches (Audebrand, 2017;Wagenaar, 2019). Prominently employment of participatory decision-making builds community capacity, reflective of the participatory governance dimension of the EMES definition (Singh & Singh, 2014;Spencer, Brueckner, Wise, & Marika, 2017;Urban & Gaffurini, 2018). Granados and Rivera (2018) suggest a flexible and decentralized structure benefits both employee and the competitive advantage of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Democratization is a term that regularly presents itself in conversations on cooperatives, yet is integral to the EMES guidelines, making it relevant across different contextual approaches (Audebrand, 2017;Wagenaar, 2019). Prominently employment of participatory decision-making builds community capacity, reflective of the participatory governance dimension of the EMES definition (Singh & Singh, 2014;Spencer, Brueckner, Wise, & Marika, 2017;Urban & Gaffurini, 2018). Granados and Rivera (2018) suggest a flexible and decentralized structure benefits both employee and the competitive advantage of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite engagement with dominant Australian society for over 200 years, Indigenous heritage, patterns of interaction, and cooperation have appreciably remained unaltered. Indigenous society has a number of unique features, including maintenance of strong spiritual and religious connection with ancestral lands [3,26], social capital in terms of relationships between members to enable the mobilization of a wide range of resources culminating in community development [37], and family values that have persistently been the bedrock of " . .…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by Martin (2017), who suggested that Western philosophies cannot be used to explore the weaknesses and possible values of Indigenous Australians [36]. Holistic and heterogeneous Indigenous Australian culture is anchored in storytelling that, as a research methodology, is culturally appropriate to reveal patterns of coherence among Aboriginal women and men when they talk about and make sense of their work related experiences [37].…”
Section: Designmentioning
confidence: 99%
“…Beyond land rights, other elements found to be key to successful Indigenous entrepreneurship include the following: identification of opportunities for entrepreneurship (Anderson 2002;Anderson et al 2003); formation of alliances, and networking among themselves and with non-Indigenous partners (including government/NGOs) (Anderson 1997(Anderson , 2002Anderson et al 2003;Berkes and Adhikari 2006;Foley and O'Connor 2013;Ord and Mazzarol 2007); capacity building through education and social enterprise (Anderson 2002;Anderson et al 2003;Cant 2007;Fleming 2015;Foley 2003;KPMG 2016;Schaper 2007;Social Ventures Australia 2016;Spencer et al 2017); enabling infrastructure (particularly internet) (Fleming 2015;KPMG 2016); institution building (Anderson 2002); culture as a key enabler (Mika et al 2017); and customary activities such as art-based activities as a key stimulator of community development (Congreve and Burgess 2017). More generally, the size of the potential customer base (Cant 2007; Commonwealth of Australia 2017b) and available workforce (Anderson 1997;Fleming 2015; Social Ventures Australia 2016) and the distance from, and access to, markets (Ord and Mazzarol 2007;Fleming 2015; Commonwealth of Australia 2017b) also play an important role.…”
Section: Conceptualising the Problemmentioning
confidence: 99%